2009
DOI: 10.1530/rep-08-0315
|View full text |Cite
|
Sign up to set email alerts
|

IGF1-induced AKT phosphorylation and cell proliferation are suppressed with the increase in PTEN during luteinization in human granulosa cells

Abstract: Granulosa cells proliferate and then undergo differentiation; an inverse relationship between these processes is observed during terminal follicular growth. During terminal follicular growth and initial luteinization, there is a necessary transition of granulosa cells to a less proliferative and highly steroidogenic form in response to LH. Although the expression of several molecules has been reported to be up-regulated by LH, proliferation/differentiation transition is not fully understood. Here, we show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 33 publications
3
29
0
1
Order By: Relevance
“…Insulin-like growth factor 1 (IGF1) is a growth factor controlling cell proliferation, differentiation, and apoptosis. Abnormal expression of IGF1 promoted metastatic activity of tumor cells [24]. IGF1 signaling is a mediator of both PI3K/AKT and ERK/P38 signaling and has been demonstrated to enhance wide variety of tumorigenesis [15,24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin-like growth factor 1 (IGF1) is a growth factor controlling cell proliferation, differentiation, and apoptosis. Abnormal expression of IGF1 promoted metastatic activity of tumor cells [24]. IGF1 signaling is a mediator of both PI3K/AKT and ERK/P38 signaling and has been demonstrated to enhance wide variety of tumorigenesis [15,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal expression of IGF1 promoted metastatic activity of tumor cells [24]. IGF1 signaling is a mediator of both PI3K/AKT and ERK/P38 signaling and has been demonstrated to enhance wide variety of tumorigenesis [15,24,25]. The emerging importance of miRNAs in the regulation of proteins associated with proliferation, survival, and PI3K/AKT pathway underscores the importance of uncovering mechanisms governing the expression of these small RNAs as a means to better understand the complicated processes of tumorigenesis and cancer cell progression [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, metformin-induced AMPK activation could inhibit the expression of cyclins D2 and E expression and consequently cell proliferation in response to IGF1 in bovine granulosa cells. AKT and MAPK3/1 are the main signaling pathways that control the growth of the granulosa cells in response to IGF1 (Hu et al 2004, Goto et al 2009). In our study, metformin did not affect IGF1-induced AKT phosphorylation (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…After activation, MAPK3/1 phosphorylates several downstream elements, including Elk-1 or P90RSK. In granulosa cells, activation of the PI3K or the MAPK pathway by IGF1 has been reported to stimulate proliferation, differentiation, and/or cell survival (Hu et al 2004, Tosca et al 2005, Goto et al 2009). Metformin treatment decreases cell proliferation of various cells including breast cancer cells and endometriotic stromal cells (Takemura et al 2007, Alimova et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Dephosphorylation of Akt with PTEN induced by LH/hCG abolished cell proliferation stimulated with IGF1 in luteinizing GCs. The results indicated that PTEN is a trigger for the proliferation/differentiation transition in human GCs (Goto et al 2009). Fan et al (2008 selectively disrupted Pten expression in GCs and mated Pten-deficient mice with transgenic mice expressing cAMP response element recombinase driven by the Cyp19 promoter.…”
Section: Pi3k/pten/akt and Tsc/mtor Pathways And Ovarian Somatic Cellsmentioning
confidence: 95%